Amino Acids in the Yamato-74662 Meteorite, an Antarctic Carbonaceous Chondrite - Shimoyama, Akira; Ponnamperuma, Cyril; Yanai, Keizo (1979)
P(論文) The Yamato-74662.23 meteorite, a carbonaceous chondrite (C2), was examined for amino acids. The meteorite sample was separated into an exterior and an interior portion. Each fraction was pulverized and extracted with water. Unhydrolyzed and acid-hydrolyzed water extracts were analyzed for amino acids, qualitatively and quantitatively. Fifteen amino acids were detected. Of these, nine amino acids are proteinaceous and six amino acids are non-proteinaceous. Glycine is the most abundant amino acid in the unhydrolyzed portion (14nm/g in the exterior and 13nm/g in the interior) and the acid-hydrolyzed portion (34nm/g in both the exterior and the interior). The D-and L-isomers of alanine, aspartic acid, and glutamic acid are nearly equal in abundance in the unhydrolyzed and hydrolyzed portions of the exterior and interior. These results clearly indicate that the amino acids detected were of meteoritic origin and few had terrestrial contaminants. departmental bulletin paper